THE DEVELOPMENT OF SCHOOL NETWORK FOR DEVELOPING CURRICULUM COPE WITH COVID-19 AND CHIANG RAI EARTHQAKE BASED ON COMPETENCY THROUGH BLENDED TRAINING AND LOCAL AREA NETWORK - Jantakoon, Jakkrit; Thanapatchotiwat, Supornthip (Journal of Education and Innovation, 2025)
This research aims to 1) developing a network of schools to develop competency-based curricula for COVID-19 and earthquake response in Chiang Rai through blended training in collaboration with local area networks 2) lessons learned from the development of school networks. The target groups were teachers, and students, of 3 schools in risky areas in Chiang Rai Province. The research was conducted using three phases of research and development methodology: Phase 1 Develop a network of schools to develop curricula, targeting 55 teachers from 3 schools. Phase 2 The network schools implement the curricula with 109 target students, And Phase 3 Lessons learned with 15 participants, including administrators, teacher representatives, student representatives, and mentor teachers. The research results found that: 1. A network of schools developing curricula to handle COVID-19 and earthquakes, focusing on competency, has increased by 3 schools, bringing the total to 8 schools. Teachers had significantly higher knowledge in developing competency-based COVID-19 and earthquake response curricula after the training than before the training at a statistical level of .05. Teachers were able to develop the curriculum and were able to design competency-based learning activities to cope with COVID-19 and earthquakes at a good level. Students from all 3 schools had significantly higher knowledge in coping with COVID-19 and earthquakes after joining the curriculum than before joining the curriculum at a statistical level of .05. They had fair skills in coping with COVID-19 and earthquakes and had the highest level of awareness of preparedness. 2. The new generation network schools have developed disaster curriculum innovations that focus on practice, are appropriate for the context, and are flexible in their implementation. The key success factors are: 1) the readiness of the knowledge platform from the research team, 2) the collaboration of the research team, mentor teachers, and local disaster networks to develop schools that are consistent with the work culture of each school’s teachers, 3) the vision of administrators, creating a leading team, and a supporting team in curriculum development, 4) the mutual vision of administrators and teachers for schools, students, and communities from curriculum development, and 5) flexibility, friendliness, trust, and positive communication among the research team, mentor teachers, administrators, and teachers in the network schools.